Chronica Slavorum. - Arnoldus, Abbot of Lübeck, -1212, author.
1 online resource.
Keywords: "The chronicle of Arnold, Abbot of the monastery of St. John of Lübeck, is one of the most important sources for the history of Germany in the central Middle Ages, and is also probably the major source for German involvement in the Crusades. The work was intended as a continuation of the earlier chronicle of Helmold of Bosau, and covers the years 1172-1209, in seven books. It was completed soon after the latter date, and the author died not long afterwards, and no later than 1214. It is thus a strictly contemporary work, which greatly enhances its value. Abbot Arnold's very readable chronicle provides a fascinating glimpse into German society in the time of the Emperor Frederick Barbarossa and his immediate successors, into a crucial period of the Crusading movement, and also into the religious mentality of the Middle Ages"--